2023
DOI: 10.3389/fchem.2023.1150565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyrolysis on iron-metal organic frameworks (MOFs) to Fe3C @ Fe5C2 for diesel production in Fischer-Tropsch Synthesis

Abstract: The Fischer-Tropsch Synthesis (FTS) is a significant catalytic chemical reaction that produces ultra-clean fuels or chemicals with added value from a syngas mixture of CO and H2 obtained from biomass, coal, or natural gas. The presence of sulfur is not considered good for producing liquid fuels for(FTS). In this study, we reveal that the presence of sulfur in ferric sulfate Fe2(SO4)3 MOF provides the high amount, 52.50% of light hydrocarbons in the carbon chain distribution. The calcined ferric nitrate Fe(NO₃)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Therefore, in the study, potassium was used as a promoter. After absorption of the biomass in the activation agent, the sample was calcined in the furnace at a high temperature (500°C–600°C) ( Munir et al, 2023 ). Finally, the prepared char was washed with HCl or distilled water to remove the excess amount of activation agent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the study, potassium was used as a promoter. After absorption of the biomass in the activation agent, the sample was calcined in the furnace at a high temperature (500°C–600°C) ( Munir et al, 2023 ). Finally, the prepared char was washed with HCl or distilled water to remove the excess amount of activation agent.…”
Section: Methodsmentioning
confidence: 99%
“…Fischer-Tropsch synthesis (FTS) is a process that has been used for the conversion of syngas (a mixture of hydrogen and carbon monoxide) into liquid fuel hydrocarbons ( Chernyak et al, 2020 ); ( Munir et al, 2023 ). A series of catalysts have been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…found that the presence of sulfur in Fe 2 (SO 4 ) 3 MOFs provided a significant amount (52.50%) of light hydrocarbons in the carbon chain distribution. 67 High-temperature annealing made the pores of the MOFs finer, improving the catalytic products' selectivity. High-temperature pyrolysis during catalyst preparation brought iron and carbon into contact more rapidly and promoted the formation of the active phase of iron carbide.…”
Section: Co Conversionmentioning
confidence: 99%
“…Furthermore, when the efficiency of a hydrogen fuel cell vehicle is two times that of an internal combustion vehicle, wind to hydrogen for hydrogen fuel cell vehicles rather than gasoline may result an economically viable GHG emissions mitigation [114]. Table 4 shows the efficiency and cost of hydrogen production from various renewable processes [115][116][117][118]. Hydrogen production from wind energy.…”
Section: Renewable Sources For Hydrogen Productionmentioning
confidence: 99%